2021
DOI: 10.1111/ctr.14395
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variance of Donor‐Derived Cell‐Free DNA (dd‐cfDNA) in Stable Kidney Transplant (KTx) patients are influenced by donor/recipient variables

Abstract: Background:The longitudinal time-course of dd-cfDNA after kidney transplant (KTx) is not well-described. The cut off values of dd-cfDNA in KTx derive from biopsycoupled single measurements. Meaningful interpretation necessitates understanding of: (1) time variance of dd-cfDNA levels post-KTx, (2) factors determining biologic variability, and (3) relationship to donor and recipient characteristics. We hypothesized that an understanding of the aforementioned factors would better inform clinical decision-making u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Relevant clinical factors should be considered when adopting this approach, such as type of donor, degree of recipient sensitization, and duration since transplant, because these may impact ddcfDNA levels independently of allograft pathology. 61…”
Section: What Does the Results Mean?mentioning
confidence: 99%
See 3 more Smart Citations
“…Relevant clinical factors should be considered when adopting this approach, such as type of donor, degree of recipient sensitization, and duration since transplant, because these may impact ddcfDNA levels independently of allograft pathology. 61…”
Section: What Does the Results Mean?mentioning
confidence: 99%
“…Given biological and technical variations in assays, validation studies have identified that, for a result to represent a clinically significant change in serial sampling, the change must exceed 61% to 66%. 61,83 Whether serial measurements of ddcfDNA could adequately account for the influence of biological variation can only be assessed in further controlled studies.…”
Section: Monitoring Response To Treatment Of Rejectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, as initial validation studies were performed on single timepoints wherein rejection was suspected and a biopsy was performed, appropriate ddcfDNA levels for given periods of time post-transplant are not well understood. Indeed, many recipient factors (e.g., panel reactive antibody [PRA], repeat transplant status) interact with donor factors (e.g., donation after circulatory death [DCD]) over time to influence ddcfDNA levels in the absence of suspicion of rejection [ 29 ]. Sureshkumar et al in 2020 conducted a retrospective study that evaluated the influence of obesity on ddcfDNA levels.…”
Section: Current Usesmentioning
confidence: 99%